The extracellular RNA complement of Escherichia coli - Ghosal, Anubrata; Upadhyaya, Bimal Babu; Fritz, Joëlle V.; Heintz‐Buschart, Anna; Desai, Mahesh S.; Yusuf, Dilmurat; Huang, David; Baumuratov, Aidos; Wang, Kai; Galas, David; Wilmes, Paul (MicrobiologyOpen (Weinheim), 2015)
The secretion of biomolecules into the extracellular milieu is a common and well‐conserved phenomenon in biology. In bacteria, secreted biomolecules are not only involved in intra‐species communication but they also play roles in inter‐kingdom exchanges and pathogenicity. To date, released products, such as small molecules, DNA, peptides, and proteins, have been well studied in bacteria. However, the bacterial extracellular RNA complement has so far not been comprehensively characterized. Here, we have analyzed, using a combination of physical characterization and high‐throughput sequencing, the extracellular RNA complement of both outer membrane vesicle (OMV)‐associated and OMV‐free RNA of the enteric Gram‐negative model bacterium Escherichia coli K‐12 substrain MG1655 and have compared it to its intracellular RNA complement. Our results demonstrate that a large part of the extracellular RNA complement is in the size range between 15 and 40 nucleotides and is derived from specific intracellular RNAs. Furthermore, RNA is associated with OMVs and the relative abundances of RNA biotypes in the intracellular, OMV and OMV‐free fractions are distinct. Apart from rRNA fragments, a significant portion of the extracellular RNA complement is composed of specific cleavage products of functionally important structural noncoding RNAs, including tRNAs, 4.5S RNA, 6S RNA, and tmRNA. In addition, the extracellular RNA pool includes RNA biotypes from cryptic prophages, intergenic, and coding regions, of which some are so far uncharacterised, for example, transcripts mapping to the fimA‐fimL and ves‐spy intergenic regions. Our study provides the first detailed characterization of the extracellular RNA complement of the enteric model bacterium E. coli. Analogous to findings in eukaryotes, our results suggest the selective export of specific RNA biotypes by E. coli, which in turn indicates a potential role for extracellular bacterial RNAs in intercellular communication. Analogous to eukaryotic cells, the enteric bacterium Escherichia coli releases RNA into its extracellular medium through shedding of outer membrane vesicles in addition to the likely involvement of secretory pathways.